2016
DOI: 10.1128/jvi.00668-16
|View full text |Cite
|
Sign up to set email alerts
|

CD95 Signaling Inhibits B Cell Receptor-Mediated Gammaherpesvirus Replication in Apoptosis-Resistant B Lymphoma Cells

Abstract: While CD95 is an apoptosis-inducing receptor and has emerged as a potential anticancer therapy target, mounting evidence shows that CD95 is also emerging as a tumor promoter by activating nonapoptotic signaling pathways. Gammaherpesviral infection is closely associated with lymphoproliferative diseases, including B cell lymphomas. The nonapoptotic function of CD95 in gammaherpesvirus-associated lymphomas is largely unknown. Here, we show that stimulation of CD95 agonist antibody drives the majority of sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Acyclovir (114798-25MGCN) was from Merck Millipore. MHV68 lytic antigen was previously described (Tan et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acyclovir (114798-25MGCN) was from Merck Millipore. MHV68 lytic antigen was previously described (Tan et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was isolated from HSV-1-GFP infected Vero cells. Real-time quantitative PCR (qPCR) was performed to measure HSV-1 viral DNA as previously described (Tan et al 2016). Total RNA isolation, cDNA synthesis and quantitative RT-PCR (qRT-PCR) to measure HSV-1 viral gene expression were performed as previously described (Tan et al 2016).…”
Section: Real-time Quantitative Pcr and Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The program T20 was used for SL-1, M12, and other selected cells, whereas the program D17 was used for CHOP knockout C-4 cells in the CHOP overexpression rescue experiments. The MHV68 RTA promoter luciferase assay was performed as described previously (54).…”
Section: Nucleofection and Luciferase Assaymentioning
confidence: 99%
“…In addition to the role in the cytotoxic activity of innate immune NK cells and pDC cells, death receptor-mediated apoptosis plays an important role in the cytotoxic T cell killing during viral infection. It is well demonstrated that some virus-specific cytotoxic T lymphocytes (CTLs) use the FasL/Fas-dependent lytic mechanism to kill virus-infected or bystander cells, such as lymphocytic choriomeningitis virus (LCMV)-infected cell lysis by LCMV-specific CD4+ CTL [ 167 ], MHC class I-restricted killing of neurons by LCMV-specific CD8+ T lymphocytes [ 168 ], Ag-bearing cell killing and non-Ag-bearing bystander cell killing by HCV-specific CTLs [ 169 , 170 ], and growth inhibition of EBV- or MHV68-infected B cells by virus-specific CTLs [ 171 , 172 , 173 ]. In addition, Fas- and TRAIL-mediated apoptosis regulate clearance of influenza A virus (IAV) by IAV-specific CD8+ T cells [ 174 , 175 ].…”
Section: Consequence Of Death Receptor-mediated Apoptosis During Vmentioning
confidence: 99%